Chatbots Made Easy: A Practical Workshop on Generative AI - Aullia, Mochammad Rizqi; Fadillah, Muhammad Daffa; Umam, Khoirul; Septiana, Dimas; Rahmawati Gunawan, Alfiana; Nurbaya Ambo, Sitti; Rosanti, Nurvelly; Ardhani, Yana; Jumail, Jumail (Edumedia Solution, 2025)
Chatbots powered by Generative AI have become a rapidly evolving technological innovation, enabling users to interact with AI-based systems in a more natural way. However, the implementation of these chatbots still faces many challenges, especially for beginners who lack a deep technical background. This study aims to develop a more accessible and understandable approach for those new to Generative AI. Through webinars and workshops, participants were introduced to the fundamentals of language models, the use of tools such as Google Colab, as well as various challenges and opportunities in AI chatbot development. Some of the main obstacles encountered included complex materials, limited access to data and computational resources, and varying levels of understanding among participants. Nevertheless, these activities provided beginners with the opportunity to grasp the basics of Generative AI and even develop their own chatbots. With a more practical and inclusive approach, this study contributes to introducing Generative AI-based chatbot technology to a broader audience. Evaluation results showed positive feedback from 77 participants from diverse backgrounds, with 51.9% stating they were very satisfied, 37.7% satisfied, and 10.4% neutral. Additionally, Pre-Test and Post-Test results indicated an improvement in participants' understanding of building simple chatbots. This initiative successfully provided a strong foundation for beginners to enter the field of Artificial Intelligence, particularly Generative AI